Respiratory health and chronic disease risks in residents of agricultural areas in Chiang Mai, Northern Thailand - Anurak Wongta; Supansa Pata; Kriangkrai Chawansuntati; Supachai Yodkeeree; Surat Hongsibsong; Woottichai Khamduang (PLoS ONE, 2025)
Respiratory health and chronic disease risks are prevalent concerns in agricultural communities in Northern Thailand, prompting an assessment of these issues among residents in Chiang Mai. A cross-sectional study involving 145 participants was conducted in San Pa Tong District from October to December 2023, utilizing structured questionnaires and spirometry tests to evaluate lung function and chronic health disease risk. The study found that education and income significantly impacted lung function, with better FVC% and FEV1/FVC% predicted values observed in those with primary education and lower income. Lower DM risk was associated with better lung function (P =  0.023). Logistic regression showed a significant increase in lung function impairment among participants with high to very high DM risk (aOR 9.06, p < 0.05). High CV and COPD risk levels also correlated with lung function impairment, though not all results were statistically significant. The results emphasize the intricate interplay between socioeconomic factors, chronic disease risks, and lung function, advocating for public health interventions that holistically address population respiratory and metabolic health.